Vals Thermal Baths - Zumthor, Peter (Washington University Open Scholarship, 1996)
Material of interest: Valser Quartzrite. Properties of material: This stone unique to the area has an unique blend of quartz and feldspar crystals giving it a green hue. https://openscholarship.wustl.edu/bcs/1108/thumbnail.jpg